Catalyst-free electrochemical dearomatization of pyridine derivatives - Wang, Kui; Tian, Yingjun; Li, Baoying; Wang, Ling; Gao, Wei; Jia, Xiaofei; Wang, Ruiming; Zhu, Yanping; Chen, Jianbin (Green synthesis and catalysis, 2024)
We demonstrated herein an electrochemical dearomatizative alkylation of Katritzky salts, wherein Katritzky salts were harnessed as both radical acceptors and donors. A wide range of privileged dihydropyridine scaffolds was constructed with good to excellent yields. Cyclic voltammetry (CV) and electron paramagnetic resonance (EPR) results confirmed the key intermediates-dihydropyridine radicals and gram-scale reaction highlighted the practical and sustainable feature of the newly developed protocol. An electrochemical dearomatizative alkylation of Katritzky salts was described, accomplishing the privileged dihydropyridine scaffolds in excellent yields. EPR and CV determination corroborate the dihydropyridine radicals via the dearomatization. [Display omitted]